2019
DOI: 10.1111/jam.14433
|View full text |Cite
|
Sign up to set email alerts
|

Zinc mediates resuscitation of lactic acid‐injuredEscherichia coliby relieving oxidative stress

Abstract: Aims Lactic acid is a natural antimicrobial in food industry, and also exists in fermented food. It was reported that sublethally injured Escherichia coli could survive in acidic conditions. When conditions become advantageous, injured E. coli can restore physiological function, which is a potential threat in food industry. Recovery is a necessary step for discriminating injured bacteria, but the resuscitation mechanism of injured bacteria is still unknown. Methods and Results In our study, sublethal lactic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…When treated with PCA only, the CAT activity significantly increased to 109.18% ( p ≤ 0.05). Shi et al [ 23 ] found that at a molecular level that gene katG , which encodes KatG enzyme (a distinct CAT), is up-regulated in E. coli after a lactic acid treatment. After the PCA + HHP treatment, the CAT activity reached a maximum (128.76%) when the pressure reached 200 MPa, and then it decreased to 96.85%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When treated with PCA only, the CAT activity significantly increased to 109.18% ( p ≤ 0.05). Shi et al [ 23 ] found that at a molecular level that gene katG , which encodes KatG enzyme (a distinct CAT), is up-regulated in E. coli after a lactic acid treatment. After the PCA + HHP treatment, the CAT activity reached a maximum (128.76%) when the pressure reached 200 MPa, and then it decreased to 96.85%.…”
Section: Resultsmentioning
confidence: 99%
“…The pellets were each re-suspended in 10 mL 1/2-MIC PCA solution, and then cultured at 37 °C for 60 min at 120 rpm. The bacterial suspension after the PCA treatment was then treated under the same conditions as the HHP group [ 23 ]. For the 0 MPa treatment of the PCA + HHP group, cells treated with 1/2-MIC PCA, were then placed in the HHP equipment for 5 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous experimental results, manganese and iron significantly improved the recovery ratio of lactic acid-injured E. coli, but whether and how manganese and iron promoted recovery by participating in oxidative stress response is still unclear (Shi et al 2017). In the genetic level, E. coli are more sensitive to acidic environmental stress after katE, katG, sodC or rpoS involved in oxidative stress resistance is knocked out (Shi et al 2019). In order to understand and design effective recovery condition of injured bacteria, the mechanisms of resuscitation need to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In the genetic level, E. coli are more sensitive to acidic environmental stress after katE , katG , sodC or rpoS involved in oxidative stress resistance is knocked out (Shi et al . 2019). In order to understand and design effective recovery condition of injured bacteria, the mechanisms of resuscitation need to be clarified.…”
Section: Introductionmentioning
confidence: 99%